Pengaruh Pemberian Ekstrak Daun Tin Terhadap Kadar Malondialdehyde Pada Tikus Putih Model Stroke Iskemik - Salsabilla, Rifdah; Rachman, Mochammad Erwin; Bakhtiar, Ilma Khaerina Amaliyah; Muchsin, Achmad Harun; Utami, Dian Fahmi (Universitas Malahayati, 2025)
ABSTRACT Oxidative stress has an important role in ischemic stroke. Malondialdehyde (MDA) is a biomarker of oxidative stress. A high MDA concentration indicates an oxidation process in the cell membrane. One plant that is thought to contain high levels of antioxidant compounds is fig leaves. Fig leaves contain flavonoid compounds which are an alternative therapy option to prevent the formation of free radicals, thus potentially improving the symptoms of ischemic stroke. The aim of this study was to analyze the effect of administering fig leaf extract (Ficus Carica L.) on MDA levels in white rats (Rattus norvegicus) ischemic stroke model. The purpose of this study was to analyze the effect of tin leaf extract (Ficus Carica L.) on MDA levels in white rats (Rattus norvegicus) ischemic stroke model. This type of research is true experimental which uses Randomized Pretest Posttest Control Group Design using experimental animals. The results showed that there is an effect of giving tin leaf extract (Ficus Carica L.) on MDA levels in white rats (Rattus norvegicus) ischemic stroke model seen in the decrease in MDA levels after being treated with the best dose to reduce MDA levels is 500 mg / kgBB. Giving this dose can reduce the highest MDA levels on the 7th day after treatment then increase on the 14th day after treatment. The conclusion of this study is giving tin leaf extract (Ficus carica L.) affects MDA levels in white rats (Rattus norvegicus) ischemic stroke model. The optimal dose to reduce MDA levels is 500 mg/kgBB, with the most significant decrease in MDA levels occurring on day 7 after treatment. These results indicate that tin leaf extract has potential as a therapeutic agent in reducing oxidative stress in ischemic stroke conditions, although the effect is temporary. Keywords: Tin Leaf Extract, Malondialdehyde Levels, White Rats, And Ischemic Stroke. ABSTRAK Stres oksidatif mempunyai peran penting dalam stroke iskemik. Malondialdehyde (MDA) adalah salah satu biomarker stres oksidatif. Konsentrasi MDA yang tinggi menunjukkan adanya proses oksidasi pada membran sel. Salah satu tanaman yang diduga memiliki kandungan senyawa antioksidan yang tinggi adalah daun tin. Daun tin mengandung senyawa flavonoid yang menjadi salah satu pilihan terapi alternatif untuk mencegah pembentukan radikal bebas sehingga berpotensi memperbaiki gejala stroke iskemik. Tujuan penelitian ini adalah menganalisis pengaruh pemberian ekstrak daun tin (Ficus Carica L.) terhadap kadar MDA pada tikus putih (Rattus norvegicus) model stroke iskemik. Jenis penelitian ini adalah true experimental yang menggunakan rancangan Randomized Pretest Posttest Control Group Design dengan menggunakan hewan coba. Hasil penelitian menunjukkan terdapat pengaruh pemberian pemberian pemberian ekstrak daun tin (Ficus Carica L.) terhadap kadar MDA pada tikus putih (Rattus norvegicus) model stroke iskemik yang terlihat pada penurunan kadar MDA setelah diberi perlakuan dengan dosis yang paling baik untuk menurunkan kadar MDA adalah sebesar 500 mg/kgBB. Pemberian dosis tersebut dapat menurunkan kadar MDA paling tinggi pada hari ke-7 setelah perlakuan kemudian meningkat pada hari ke-14 setelah perlakuan. Pemberian ekstrak daun tin (Ficus carica L.) berpengaruh terhadap kadar MDA pada tikus putih (Rattus norvegicus) model stroke iskemik. Dosis optimal untuk menurunkan kadar MDA adalah 500 mg/kgBB, dengan penurunan kadar MDA paling signifikan terjadi pada hari ke-7 setelah perlakuan. Hasil ini mengindikasikan bahwa ekstrak daun tin memiliki potensi sebagai agen terapeutik dalam mengurangi stres oksidatif pada kondisi stroke iskemik, meskipun efeknya bersifat sementara. Kata Kunci: Ekstrak Daun Tin, Kadar Malondialdehyde, Tikus Putih, dan Stroke Iskemik